2017
DOI: 10.1016/j.ijrobp.2017.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up on NRG Oncology RTOG 0915 (NCCTG N0927): A Randomized Phase 2 Study Comparing 2 Stereotactic Body Radiation Therapy Schedules for Medically Inoperable Patients with Stage I Peripheral Non–small Cell Lung Cancer

Abstract: Materials/Methods: Forty-two EC patients were enrolled in this ongoing prospective imaging study. For this report, we report on the 20 patients who had surgery after neoadjuvant CRT. Outcome was assessed pathologically based on tumor regression grade (TRG, 1 Z pathologic complete response, 2 Z near complete response, and 3 Z more than minimal residual). FDG PET imaging was acquired before treatment (baseline, BL), approximately 2 weeks after starting chemoradiation (interim, IM), and at first follow-up (FU) 4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 0 publications
2
61
0
Order By: Relevance
“…Due to the recent technological advances in lung stereotactic body radiation therapy (SBRT) treatments and reported comparable tumor local‐control rates,single‐dose lung SBRT has become a viable treatment option for peripherally located lung lesions for medically inoperable early‐stage nonsmall‐cell lung cancer (NSCLC) patients . Additionally, there has been growing interest in the clinical use of flattening filter‐free (FFF) beams to deliver lung SBRT treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the recent technological advances in lung stereotactic body radiation therapy (SBRT) treatments and reported comparable tumor local‐control rates,single‐dose lung SBRT has become a viable treatment option for peripherally located lung lesions for medically inoperable early‐stage nonsmall‐cell lung cancer (NSCLC) patients . Additionally, there has been growing interest in the clinical use of flattening filter‐free (FFF) beams to deliver lung SBRT treatment .…”
Section: Introductionmentioning
confidence: 99%
“…The use of single‐fraction lung SBRT treatments has been previously studied . For instance, Siva et al reported comparable local control rates, overall survival and toxicity profiles between single dose of 26 Gy for peripheral tumors and 18 Gy for centrally located tumors compared to 48 Gy in 4 fractions for peripheral tumors and 50 Gy in 5 fractions for the central tumors for patients with FDG‐PET staged pulmonary oligometastases.…”
Section: Discussionmentioning
confidence: 99%
“…SBRT protocol RTOG‐0915 (Arm 1) allowed a single dose of 34 Gy treatment for early stage I peripheral NSCLC patients when dosimetric criteria were achieved . Videtic et al reported long‐term follow‐up data, which revealed no excess late toxicity in either arm (34 Gy in 1 fraction and 48 Gy in 4 fractions), coupled with consistent high rates of local control. The median overall survival of 4 yr for each arm suggests similar efficacy.…”
Section: Introductionmentioning
confidence: 90%
“…[1][2][3][4][5] For the selected peripherally located NSCLC patients; single-dose of SBRT has become a curative treatment option as shown by the randomized trials. [6][7][8][9][10][11][12][13] For instance, Videtic and colleagues 7 compared 2 single-fraction SBRT dosing schemes of 30 and 34 Gy for 80 medically inoperable early stage-I NSCLC patients. Both treatment schedules provided similar tumor local-control and overall survival rates with minimal pulmonary toxicity.…”
Section: Introductionmentioning
confidence: 99%